Ethical issues relating to qualitative research - J. Jelsma; S. Clow (AOSIS, 2005)
Qualitative research or naturalistic research has moved from the sidelines into the mainstream of health research and an increasing number of qualitative research proposals are being presented for ethical review Qualitative research presents ethical problems that which are unique to the intensive hands-on paradigm which characterises naturalistic research. This paper briefly outlines the most common methodologies used in this research. The four ethical principles of benevolence, non-maleficence, autonomy and justice will be used as a framework to explore specific ethical issues related to this form of inquiry. The need for scientific rigour will also be explored as research that is scientifically unsound can never be ethical.